Effects of Melatonin and Coenzyme Q 10 Added to Extenders on Spermatological Properties in Cryopreservation of Epididymal Rat Sperm - Yılmaz Dayanç, F; Yıldız, C (Journal of the Hellenic Veterinary Medical Society, 2025)
With the use of advanced genome editing technology, the production of genetically modified mutant rats worldwide, and the successful freezing and storage of their gametes, have become important in biotechnology. In the present study, the effects of different doses of melatonin (0.5mM, 1mM, 2mM) and coenzyme Q10 (25µM, 50µM, 75µM) added to the spermatozoon freezing medium containing 8% lactose monohydrate, 23% egg yolk (EY), and 10% trisaminomethane on the freezability of rat spermatozoa were investigated. After freezing and thawing, motility, dead spermatozoa rate, plasma membrane integrity, abnormal acrosome rate, motility longevity, apoptotic and necrotic cell rates were evaluated. Compared to the control group (12.90±1.34%), the highest motility value was found in the 1mM Melatonin group (24.58±1.68%) and 25µM Coenzyme Q10 group (24.23±1.95%) (p<0.01). The lowest dead spermatozoa rate was determined in the 1mM Melatonin group (63.08±4.89%) compared to the control group (75.47±2.27%) (p<0.01). Plasma membrane integrity rates were higher in the 1mM Melatonin (35.50±1.82%) and 25µM Coenzyme Q10 (31.31±1.93%) groups compared to the control group (18.21±1.36%) (p<0.01). The best motility longevity was observed in the 1mM melatonin and 25µM coenzyme Q10 groups compared to the control group (p<0.01). There was no difference between the groups in terms of abnormal acrosome rates (p>0.01). Apoptotic and necrotic cell rates were found to be lower in the 1mM Melatonin or 25µM Coenzyme Q10 groups compared to the control group (p<0.01). However, it was found that the use of 1mM melatonin had a better protective effect than 25µM coenzyme Q10 (p<0.01). In conclusion, the addition of 1mM Melatonin or 25µM Coenzyme Q10 to the rat sperm diluent effectively protected spermatozoa against cryo-damage during cryopreservation process.